Prevalence of hypertension and associated factors in Jalalabad City, Nangarhar Province, Afghanistan - Khwaja Mir Islam Saeed (University Library System, University of Pittsburgh, 2015)
Background: Hypertension affects an estimated one billion people, worldwide. It is a public health challenge characterized by increased morbidity, mortality, as well as cost to the community and health systems. The goal of this study is to determine the prevalence of hypertension and characterize associated risk factors in an urban setting in Afghanistan. Methods: A cross-sectional study of adults aged 25-65 years was conducted in Jalalabad city from May to June 2013 using the World Health Organization STEPwise approach to surveillance (WHO STEPS). A multistage technique was used to enroll 1,200 participants in the study. Demographic and socio-economic variables were collected via individual interviews using the WHO STEPS survey, after which blood samples were collected using a locally developed standard operating procedure (SOP). Bivariate and multivariable analyses were performed to explore the association between hypertension and associated factors. Results: A total of 1,180 adults (40% males, 60% females) of 25-65 years of age were surveyed. The response rate was 98.5 % and the prevalence of hypertension was 28.4. Independent risk factors of hypertension were found to be: age ≥ 50 (AOR = 3.42, 95% CI: 2.50 - 4.76); sex (AOR = 0.58, 95% CI: 0.38 - 0.88); obesity (AOR = 2.1, 95% CI 1.49 - 2.94); and diabetes (AOR = 1.75, 95% CI: 1.10 - 2.79). Independent protective factors were physically demanding occupations (AOR = 0.55, 95% CI: 0.36 - 0.85); physical activity itself (AOR = 0.69, 95% CI: 0.47 - 0.99) and consuming more vegetables (AOR = 0.59, 95% CI: 0.38 - 0.93). Conclusion: This urban setting in Afghanistan evidenced a high prevalence of hypertension; age, obesity, and diabetes were identified as risk factors and physical activity and consuming more vegetables were protective. These findings have implications for future public health intervention and clinical efforts.